Trench filling with phosphorus-doped monocrystalline and polycrystalline silicon. (15th June 2022) - Lespiaux, J.; Deprat, F.; Rodrigues Goncalves, B.; Souc, J.; Leverd, F.; Juhel, M.; Mattei, J.-G.; Giroud-Garampon, C.; Roman, A.; Magis, T.; Hartmann, J.M.
Abstract: Optimized epitaxial processes for the filling of deep trenches are mandatory for the fabrication of advanced devices in the microelectronic industry. The use of Selective Epitaxial Growth (SEG) in deep cavities faces multiple issues such as inhomogeneities along the growth direction or defect formation. In this work, the main objective was to develop void-free processes to fill 1:6 up to 1:16 aspect ratio trenches with monocrystalline and polycrystalline Si:P respectively, in a Reduced Pressure – Chemical Vapour Deposition (RP-CVD) reactor. Previous studies suggested the use of a SiH2 Cl2 (DCS) + PH3  + HCl chemistry, with an optimization of the DCS/HCl mass-flow ratio (MFR) to conformally fill large and high aspect ratio trenches with monocrystalline Si:P (c-Si:P) while preventing overgrowth at the trench entrance and voids at the bottom. Current studies were first of all conducted on blanket wafers at T = 950 °C and P = 10 Torr, in order to choose the best strategy for varying DCS/HCl MFRs. The P + ions concentration was quantified and two trends were highlighted depending on the PH3 partial pressure (P(PH3 )). For P(PH3 ) lower than 10 -5  Torr, the dopant concentration (in the 10 17 - 10 18  cm -3 range) increased solely with the phosphine flow and did not depend on the HCl flow. Meanwhile, for PH3 partial pressures higher than 10 -5  Torr and thus higher doping levels (between 3x10 18 and 2x10 19 cm -3 ), the P + ions concentration increased with the PH3 flow and decreased as the HCl flow increased. The filling of 1:6 aspect ratio trenches by monocrystalline Si:P was then achieved thanks to a three steps process with various DCS/HCl MFRs. Characterizations showed good crystalline quality together with a steady doping level of 1.3x10 18  at cm -3 . Further optimizations will however be required to completely suppress voids. Meanwhile, the filling of 1:16 aspect ratio trenches or needles by poly-Si:P was successfully achieved at 10 Torr with a SiH4  + PH3 chemistry, provided that the deposition temperature, 750°C, was low enough to avoid the formation of large poly-Si:P grains, notably at the entrance of such cavities. Highlights: Sequential epitaxial growths to fill 1:6 and 1:16 aspect ratio trenches in Si. 950 °C and 10 Torr to fill trenches with monocrystalline Si:P 10 18 –10 19  at cm -3 SiH2 Cl2 /HCl mass flow ratios optimization to have void-free trench filling. Low temperatures minimize voids and grain sizes when filling trenches with poly-Si:P. 750 °C and 10 Torr to fill, thanks to SiH4, 1:16 cavities with poly-Si:P 10 19  at cm -3